2014
DOI: 10.1016/j.ahj.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alirocumab, a monoclonal antibody to PCSK9, on long-term cardiovascular outcomes following acute coronary syndromes: Rationale and design of the ODYSSEY Outcomes trial

Abstract: ODYSSEY Outcomes will determine whether the addition of the PCSK9 antibody alirocumab to intensive statin therapy reduces cardiovascular morbidity and mortality after ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
239
0
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 377 publications
(248 citation statements)
references
References 30 publications
0
239
0
9
Order By: Relevance
“…Furthermore, although the CTT Collaboration had a greater number of women than our study (4416 versus 1887), the LDL‐C achieved was much higher; the findings in our analysis, therefore, add to earlier results. Indeed, demonstration of a continuum of benefit through to very‐low levels of LDL‐C, in a lower‐risk population in this pooled analysis than the populations studied in the FOURIER8 and ODYSSEY OUTCOMES12 trials, should be considered complimentary data.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, although the CTT Collaboration had a greater number of women than our study (4416 versus 1887), the LDL‐C achieved was much higher; the findings in our analysis, therefore, add to earlier results. Indeed, demonstration of a continuum of benefit through to very‐low levels of LDL‐C, in a lower‐risk population in this pooled analysis than the populations studied in the FOURIER8 and ODYSSEY OUTCOMES12 trials, should be considered complimentary data.…”
Section: Discussionmentioning
confidence: 96%
“…MACE were defined according to the primary end point of the ODYSSEY OUTCOMES trial as the composite of coronary heart disease death, nonfatal myocardial infarction, ischemic stroke, or diagnosis of unstable angina (limited to events with evidence of ischemia and fulfilling additional severity criteria, requiring hospitalization or emergency department visit until at least the following day), whichever came first 10, 12. As per the ODYSSEY OUTCOMES trial, all cardiovascular events were adjudicated by a central Clinical Events Committee 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing ODYSSEY OUTCOMES trial will capture diabetes and prediabetes reported by investigators, as well as by serial HbA 1c and FPG measurements in >18 000 high‐risk individuals with 2–5 years of follow‐up, and will allow further analyses and provide longer‐term data on whether alirocumab has any effects on glycaemic measures and the development of diabetes 25.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the SPIRE (bococizumab) has been terminated, probably due to signs of an immune response to the drug (25). The ODYSSEY outcomes (alirocumab) and FOURIER (evolocumab) trials are still underway to provide confirmation of the actual clinical benefit of PCSK9 inhibitors (26). While waiting for the results of those hard endpoint phase III clinical trials, the imaging GLAGOV trial (evolocumab) has shown that the reduction in lipid levels translates into a significant effect on atherosclerotic plaque stabilisation and regression (27).…”
Section: Presentmentioning
confidence: 99%